Concentration and balance: Factors influencing successful shooting in basketball - Rachmad Nur Cahya; Achmad Suparto; Dyas Andry Prasetyo (Universitas Sriwijaya, 2021)
The purpose of this study was to determine the relationship between the level of concentration and balance on shooting under basketball of Taruna Sumenep club players. This study uses a non-experimental research type with a correlational research design. The research instrument used a Grid Concetration Test questionnaire for concentration variables, 30 seconds of shooting under basket, and a balance test. The sample of this study amounted to 12 athletes, with purposive sampling technique. Data analysis used correlation product moment. The results showed that there was no relationship between concentration and under basket with the significance value of 0,364. For the balance variable with under basket the significance value is 0,940, which means there is no relationship. The conclusion that can be drawn from this study is that there is no significant relationship between balance and under basket and concentration with under basket.